Performance of Seawater Activated Battery as Alternative Energy Resources - Masrufaiyah; Ridho Hantoro; Gunawan Nugroho; Totok R. Biyanto; Nur Laila Hamidah (IPTEK The Journal of Engineering, 2017)
Research on Freshwater and Seawater batteries, which using Al and Cu electrodes at variation of different electrolyte salinity, distance between electrodes and flowrate of electrolyte has been carried out. The galvanostatic discharge and Electrochemical Impedance Spectroscopy (EIS) of Al and Cu in seawater were investigated. The results showed the optimum condition with significant average potential discharge of 45,02 mV and current of 0,440 mA obtained from combination of 5% electrolyte salinity, 2 cm space between electrodes and 0,5 liter/hour electrolyte rate. EIS studies revealed that the Al and Cu interficial electrochemical process in seawater was determined by an activation controlled reaction.